DEVELOPMENT OF VIDEO ANIMATION “A DAY WITH NIKA & BIMA” TO IMPROVE SPEAKING SKILLS OF GRADE 1 ELEMENTARY STUDENTS IN GREETINGS - Ar Risydah Futari No Ai De Sousa; Babang Robandi; Effy Mulyasari (Wiralodra English Journal, 2026)
First grade students often quickly feel bored when learning English, especially in speaking, because of how unsuitable the learning material that’s used. English needs to be conquer in early ages because based from “Critical Period”, in early ages, children can conquer new languages more significantly than adults. Based on this, this research aims to improve the speaking skills of first grade students in Greetings by using video animation. The difference between the video animation for this research than the previous video animation’s that the video animation that’s developed for this research “A Day with Nika & Bima” use the POV as if the characters are doing vlog. This research uses the D&D and ADDIE as its development model. The instruments that were used were interviews, observations, questionnaires, and tests. Likert scale was used for validation questionnaire research by experts and student response questionnaires. The validation by experts showed that the media was very feasible to use, while the results of the pre-test and post-test showed increases in the average student results by 33.17%, with the results of N-gain = 0.90 (high category), with 78.16% (satisfied) from students’ questionnaires, shows that using video animation, students can improve their English-speaking skills.